The Evaluation of Students' Religious Development at School - Baharudin, Parid; Kurahman, Opik Taupik (Universitas Islam Negeri Raden Intan Lampung, 2022)
This research aims to identify and analyze the fundamental concepts of evaluation in the development of student diversity in schools. The evaluation of the religious development program reveals how far students' religious development has progressed at school. This study utilized a qualitative approach with library research, in which data is collected from readings and then analyzed and concluded about the issues discussed. According to the findings, evaluating students' religious development in schools is carried out by assessing and measuring religious development programs in schools, both curricular and extracurricular. So it can be cConcluded, assessing and measuring students' religious development in schools focuses on assessing religiosity (spiritual), attitudes, and knowledge skills.